MEKANISME DAN STRUKTUR PASAR ISLAM ANTARA IDEALITA DAN REALITA: TELAAH KRITIS PEMIKIRAN EKONOMI ISLAM - Zakiyatun Nufus; Nurlaili (Jurnal At Taajir, 2021)
At that time the market mechanism was highly valued. The Prophet refused to make a price fixing policy when the price level in Medina at that time suddenly rose. As long as the increase occurs due to pure supply and demand forces, which are not accompanied by monopolistic and monopsonistic drives, there is no reason not to respect market prices. In a Hadith it is explained that the market is a natural law (Sunnatullah) that must be upheld. No one individually caninfluence the market, because the market is a collective force that has become the provision of Allah SWT. Violation of market prices, for example fixing prices in a way and for inappropriate reasons, is an injustice that will be held accountable before Allah and vice versa. Islamic respect for market mechanisms is based on the provisions of Allah SWT that trade must be carried out both by liking and consensual and absolute moral values must be upheld. Inparticular, moral values that receive important attention in the market are fair competition, honesty, openness and fairness.